Israel's dead soul - Salaita, Steven, 1975- (Temple University Press, 2011)
In his courageous book, Israel's Dead Soul, Steven Salaita explores the failures of Zionism as a political and ethical discourse. He argues that endowing nation-states with souls is a dangerous phenomenon because it privileges institutions and corporations rather than human beings.